Sardegna GeoBlog: gestione del territorio 2.0 (GEOmedia, 2009)
Sardegna GeoBlog: land management 2.0Sardegna GeoBlog is an innovative social networking instrument designed to support the exchange between managers that work on land management. Sardegna GeoBlog is based on a WordPress blogging platform and allows users to collect and share suggestions, articles and comments on various aspects of a specific project. The solution works under the regional Geographic Information System and it is totally Open Source. The article features an interview with Marco Melis, general manager of the land urban planning section of Sardinia Region.